Right Coronary Artery Arising from the Main Pulmonary Artery: Evaluation with 2-Dimensional Transthoracic Echocardiography and Multislice Computed Tomography - Li, Rong-Juan (Texas Heart Institute, 2010)
WEB SITE FEATURE